Peculiarities of remote identification of labor mode and rest of a driver in the vehicle information monitoring system (Transport systems and technologies, 2020)
The existing systems of remote monitoring of the parameters of the condition of vehicles and modes of work and rest of drivers do not provide an opportunity to obtain system information in sufficient volume about the change of parameters of the condition of vehicles in accordance with the changes of modes of work and rest and qualifications and experience of drivers. To solve this problem, the authors propose to conduct a study that aims to establish and develop systematic methods and tools that allow remote monitoring of the technical condition of the truck (bus) and the mode of work and rest of drivers, taking into account their operating conditions. As a result of the work, the analysis of features of remote determination of modes of work and rest of the driver in the system of information monitoring of vehicles in Ukraine was performed. A structural and logical scheme of solving the problem of determining the technical condition of vehicles and modes of work and rest of drivers in the system of information monitoring of vehicles has been developed. The developed scheme provides for the development of a system of information monitoring of the technical condition of vehicles and modes of work and rest of drivers in operating conditions at six consecutive stages of the study.
Keywords: monitoring information systems, vehicle, driver's mode of work and rest.